Characterization of Mandai Powder Encapsulants: A Comprehensive Analysis of Chemical Composition and Morphological Changes - Rohmah, Miftakhur; Apriyadi, Rimbawan; Rahmadi, Anton (Indonesian Food Science and Technology Journal, 2025)
Abstract— Potential: Mandai cempedak powder, rich in phenolic compounds and lactic acid, is encapsulated using a spray drying technique to maintain its unique content. This research aims to authenticate the final encapsulant product of Mandai powder by comparing it with raw materials (cempedak powder, Mandai powder) and the pre-encapsulation process. The analysis involves ATR FTIR, GC-MS techniques, morphological characteristics, and amino acid content. FTIR results identified lactic acid in the form of a carboxylic acid (-COOH) functional group and phenolic compounds with aromatic rings stretching carbon-carbon (C-C) bonds in starch and protein-based matrices, GC-MS analysis showed changes in volatile composition such as the appearance of the compound paromomycin, and Ethyl 9-hexadecenoic in mandai powder encapsulant products. Morphological characteristics also showed changes in structure from cempedak powder to mandai powder encapsulant. Apart from that, the amino acid content analysis in the encapsulant still detected relatively high levels of aspartic acid, glutamate, and arginine. In conclusion, this study discusses the successful encapsulation of mandai powder and provides information about changes in chemical composition during the encapsulation process.